2019
DOI: 10.1088/2053-1583/aafd3c
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Schottky barriers in ultrathin black phosphorus field effect transistors via polymer capping

Abstract: It is still a great challenge to avoid the degradation of ultrathin black phosphorus (BP) since its discovery in 2014. Various methods have been explored to stabilize the properties of ultrathin BP through capping technology or chemical passivation. Besides, the large metal-semiconductor contact resistance is also one of the critical issues. The two problems hinder the further development of ultrathin BP devices. Herein, we demonstrate that polymethyl methacrylate (PMMA) capping can not only enhance the durabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 77 publications
1
7
0
Order By: Relevance
“…Beyond the CNP [III to IV], the drain current ( I d ) starts increasing as the system becomes n-type because of excessive electron doping. In dark condition, the minimum drain current is observed for applied gate voltage at V g = 58.5 V (Figure a), which is the CNP of the BP FET and matches well with the previously reported results of BP. , However, under laser illumination, a significant shift in CNP toward the lower (but positive) V g is observed. With the increase in laser power from 0.17 to 22.63 mW, the CNP seems to lower further (inset of Figure a).…”
Section: Resultssupporting
confidence: 91%
“…Beyond the CNP [III to IV], the drain current ( I d ) starts increasing as the system becomes n-type because of excessive electron doping. In dark condition, the minimum drain current is observed for applied gate voltage at V g = 58.5 V (Figure a), which is the CNP of the BP FET and matches well with the previously reported results of BP. , However, under laser illumination, a significant shift in CNP toward the lower (but positive) V g is observed. With the increase in laser power from 0.17 to 22.63 mW, the CNP seems to lower further (inset of Figure a).…”
Section: Resultssupporting
confidence: 91%
“…The transistor covered with PMMA has a slightly larger hysteresis because PMMA can contribute to charge trapping. Indeed, it has been reported by Li et al [58] that the PMMA layer induces positive fixed charges at the interface that need to be balanced by an equal amount of charges with opposite sign in the BP. This process leads to a reduction of the effective Schottky barrier for electrons and to an increase of the effective Schottky barriers for holes, resulting in a negative shift of the charge neutral point and a reduction of the OFF state drain current.…”
Section: Resultsmentioning
confidence: 99%
“…[ 62 ] In addition, Li et al demonstrated that the polymethyl methacrylate (PMMA) cap could effectively and nondestructively improve the durability of the ultrathin BP. [ 65 ]…”
Section: Methods Of Stabilizing Bpmentioning
confidence: 99%